RELIGIOUS AND SOCIO-DEMOGRAPHIC FACTORS INFLUENCING UTILIZATION OF ANTENATAL CARE SERVICES IN ILESA, OSUN STATE, NIGERIA (2015)
Inadequate access to Ante-Natal Care (ANC) services is one of the factors responsible for high maternal and infant mortalities in Nigeria. Studies have focused on clinical determinants of pregnancy outcomes with little attention paid to belief systems and characteristic features of pregnant women who utilise ANC in spite of the potential role of religious beliefs system on pregnant women’s choice of health care services. This study, therefore, examined the influence of belief systems and socio-demographic characteristics of pregnant women on utilisation of ANC services in Ilesa, Osun State. Functionalist Theory and Health Belief Model (HBM) were used. Multistage sampling technique was used to select 500 pregnant women at household level (50), faith homes (225) and health centres (225). Ilesa was purposefully selected because of the preponderance of Faith Based Birth Homes (FBBH). Questionnaire was utilised to obtain quantitative data on socio-demographic characteristics, perception of aetiology of pregnancy complications, influence of religious beliefs, adherence to care givers’ prescriptions and husbands' roles in pregnancy care. Qualitative data were collected through non-participant observation of 20 sessions of ANC and prayer meetings. In addition, 12 In-Depth Interviews (IDIs) were conducted in each FBBH and orthodox health care institution. Quantitative data were analysed using descriptive and Chi-Square statistics at p< 0.05. Ethnographic summary was used to analyse qualitative data. Respondents’ age was 29.5 + 5years, 86.6% were Christians, 74.6% were married and 30.6% had tertiary education. About 80% attended ANC; and of this, 24.6% had their last babies in FBBH while 11.8% delivered at home. Less than 40.0% completed minimum requirements of four ANC visits. Only 51.6% had ante-natal ultra sound evaluations, 37.6% took two shots of tetanus toxoid while 18.2% refused any form of immunization as a result of religious belief. Adultery (43.8%) and activities of witches and wizards (41.6%) were perceived as causes of pregnancy complications. There was no significant relationship between religious affiliation and place of delivery. Decision making on utilisation of ANC services reflected dominant gender structure as 61.9% of respondents reported that husbands determined the choice of place of delivery. There was no significant relationship between demographic characteristics of pregnant women and ANC utilisation; age (t= .649), marital status (t=1.038), education (t= -.356) and income (t= -.356) were not significantly related to ANC utilisation. Majority of the IDIs revealed that respondents perceived pregnancy processes and outcomes as more spiritual than medical. Praying, confessions of sins, application of anointing-oil and spiritual baths were perceived as efficacious for warding off evil forces. The ANC providers in FBBH reported that many women could not afford delivery materials thereby causing some husbands to abscond on the day of delivery. Faith Based Birth Homes enjoyed more patronage than orthodox birth homes. Therefore, there is need for supportive supervision of FBBH by health professionals.